Biuletyn Informacyjny . aktualności życia publicznego, no. 11, 1977 - for ed. committee Joanna Szczęsna, Seweryn Blumsztajn, Jan Lityński (s.n.], 1977)
Creation and circulation: First issues typewritten and carbon-copied by various persons, also in fragments, there exist xerox copies of the typescript.